Developing a Virtual Reality Application of the Lawang Sewu Building as Educational Media for the Subject of History - Agus Suryanto; Diah Ayu Kusumawati (Faculty of Engineering, Universitas Negeri Yogyakarta, 2017)
Lawang Sewu is one of the Dutch colonial heritage building in Indonesia that has unique architecture as the main attraction. This building is located in Semarang, Central Java, Indonesia. Potentials of Lawang Sewu has not been conveyed due to lack of recognition efforts to society. One of the effort that can be done is to utilize virtual reality (VR) technology to provide information and enhance tourist objects. Virtual reality allows the user to interact with virtual objects as if in real life. This paper discusses about making virtual reality application which is applied as a means of introducing Lawang Sewu. This study was categorized as research and development (RD). This application runs on mobile devices running on android operating system equipped with gyroscope sensors. This application must be accompanied with an enhancement of VR cardboards. Virtual reality allows users to view and interact virtually with tourism object. The purpose of making this application is to introduce about Lawang Sewu for all of people especially students.